The Role of Vascularized Bone Graft in the Treatment of Kienbock’s Disease - Abdulkareem M. Hamid; Anmar Hamid Abdul Majeed (Diyala Journal of Medicine, 2025)
Background: Kienbock's disease, also known as avascular necrosis of the lunate, is characterized by a sequence of lunate collapse, carpal changes, and degeneration resulting from a combination of anatomic, vascular, and traumatic insults. The methods of treatment of Kienbock's disease vary according to the stage of the disease. Objectives: Evaluate the clinical and functional outcome of the pronator quadratus pedicled bone graft in the treatment of avascular necrosis of the lunate bone. Patients and Methods: A prospective case-series study was conducted at Al-Wasity Teaching Hospital from September 1, 2023, to October 1, 2024. The follow-up period was approximately six months for eight patients, whose ages ranged from 22 to 36 years (mean age, 29). Five males and three females among those patients were affected in the right hand, and three were affected in the left hand; all affected hands were the dominant ones. They presented with a history of vague wrist pain and restriction of wrist movement. These patients were later diagnosed as Kienböck disease; all of them were stage two and stage three-A. Patients were surgically treated at Al-Wasity teaching hospital by vascularized bone graft (distal radius transfer on pronator quadratus pedicle). Results: The patients included in this study were followed for a period of six months. The clinical assessment was good, as indicated by the DASH scoring system, the Mayo scoring system, and the patient's clinical and functional outcomes. Functional improvement in power grip strength was evident, with the patients' mean grip strength increasing from 147.5 mmHg preoperatively to 163.75 mmHg postoperatively. Regarding the range of motion, mean flexion-extension preoperatively was 64.37-60.62, and postoperatively, it was 71.87-65. Conclusion: The pronator quadratus pedicle bone graft is a beneficial procedure for treating patients with stage two and stage three (A) Kienbock's disease. Keywords: Kienbock's disease, Stage 2, Stage 3-A, Vascularized bone graft.